2018
DOI: 10.1007/s12098-018-2739-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Accuracy of Different Sites for Transcutaneous Bilirubin Measurement in Early Preterm Infants

Abstract: Transcutaneous bilirubin measurement is an acceptable method for identification of hyperbilirubinemia requiring treatment in early preterm newborns. The authors recommend interscapular region as a reliable site in infants of gestational age ≤34 wk for measuring transcutaneous bilirubin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
4
16
2
Order By: Relevance
“…Some studies have tested a singular site, 4,6,7,9,10 while others have examined multiple sites for comparison. 3,[11][12][13][14][15][16] The recommendation of the optimal site for TcB measurements in premature infants is conflicting in the literature. The question is further complicated by many variables such as GA, birth weight, and ethnicity.…”
mentioning
confidence: 99%
“…Some studies have tested a singular site, 4,6,7,9,10 while others have examined multiple sites for comparison. 3,[11][12][13][14][15][16] The recommendation of the optimal site for TcB measurements in premature infants is conflicting in the literature. The question is further complicated by many variables such as GA, birth weight, and ethnicity.…”
mentioning
confidence: 99%
“…However, there is some doubt regarding the use of TcB as a complete replacement for TSB [7], especially in preterm and low birth weight infants [8]. Although some studies have reported that TcB is less accurate in preterm infants than in full-term infants, a greater number of studies have reported that TcB is an accurate and reasonable alternative to TSB in preterm infants [9][10][11]. Furthermore, many recent reports have verified the accuracy and usefulness of TcB in preterm and low birth weight infants [12].…”
Section: Discussionmentioning
confidence: 99%
“…In real clinical practice, we have mostly used the forehead and sternum for TcB assessment. Some reports have used other sites, such as the interscapular space, hipbone, abdomen [10], and patchcovered skin; however, these sites are not commonly used in real clinical practice. Additionally, although TcB assessment at covered skin (r = 0.80) has been shown to be much better than TcB assessment at uncovered skin, the use of a patch is not convenient [2,19].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Agrawal et al in a study published in this issue of the journal, evaluate the correlation and diagnostic performance of TcB measured at different body sites with STB in preterm neonates born at less than 35 wks of gestation. [5] TcB measured at interscapular area was found to have best correlation with STB and highest sensitivity for diagnosing the need of phototherapy. However, even for intrascapular area, the 95% CI for agreement between STB and TcB ranged from −4.3 to +5.4 mg/dL.…”
mentioning
confidence: 89%